PENGEMBANGAN BUKU AJAR BERBASIS MITIGASI BENCANA GUNUNG BERAPI DI LUMAJANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD KELAS V - Lyza Dwi Safitri; Nuriman; Arik Aguk Wardoyo (Universitas Negeri Surabaya, 2023)
Education in the 21st century students are required to follow the development of the current learning model, teachers must provide and utilize a variety of teaching materials in order to attract students' learning interest in achieving learning goals. This study aims to develop a textbook on post-eruption volcanic management in Lumajang. This type of research is Research and Development (R&D) development research using the Borg & Gall model which includes 10 steps, and is simplified into 8 stages in this study. The method used is interviews, tests and student responses. The data analysis technique uses descriptive statistics by interpreting the research results to get the average and proportion. Based on the results of the product validity test for textbooks based on volcanic fires, it showed a score of 84.8% in the very feasible category and the score from the student response questionnaire to textbooks showed a score of 84.73% in the very feasible category. The results of the proportion of total student completeness is 89.4% which indicates that learning using development products is effectively used to improve student learning outcomes. From these results, the textbooks that have been developed can be used when learning takes place in the classroom, this is to add new insights to new knowledge for students. From this research it is hoped that it will be able to encourage students to provide an understanding of the importance of reducing education and be able to apply the occurrence of an eruption.